The Use of Tax and Nontax Provisions and Allowances - Honková, Irena (Springer, 2018)
The basic principle of the creation of accounting provisions and allowances is the principle of prudence and a true and fair view of the entity. The allowances are used to express a temporary reduction in the value of assets, while the provisions are a source of increasing costs intended to cover future debts or expenses, of which purpose is likely to incur but the amount or the date on which they arise are uncertain. There was a questionnaire survey, which was attended by 673 enterprises. The goal was to determine whether the size and scope of enterprises are linked to the creation of provisions and allowances. It was not found out that the creation of provisions and allowances depends on the size and industry of enterprises. The different types of provisions and allowances and their representation in enterprises were also examined. It was found out that 39% of businesses have never created any provisions and allowances. Most often nontax provisions (21%) are created. As a result, insufficient creation of provisions and allowances was found out.
Využití daňových a nedaňových rezerv a opravných položek
Keywords: Accounting provisions; Allowances; Czech accounting standards; Účetní rezervy; Opravné položky; České účetní standardy